Enhancing Maritime Security through Strategic Intelligence: The Relevance of the Global Maritime Axis to Indonesia's National Resilience - Fita, Gia Ayu (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2025)
This study aims to analyze the role of strategic intelligence in enhancing Indonesia's maritime security within the framework of the Global Maritime Axis (GMA). In the context of complex maritime security challenges, this research explores how strategic intelligence supports the implementation of effective maritime policies to address non-traditional threats such as illegal fishing and irregular migration. Employing a descriptive analytical method and utilizing stakeholder analysis, this study evaluates the roles, synergies, and challenges among key actors in Indonesia's maritime security framework. The maritime security concept serves as the foundation for understanding Indonesia's strategic environment, addressing both traditional security threats, such as territorial disputes and naval defense, and non-traditional challenges like transnational crime and environmental degradation. Strategic intelligence is employed to assess intelligence-driven approaches in threat detection, policy formulation, and inter-agency coordination. This study examines the Global Maritime Axis framework to evaluate its role in integrating maritime security strategies with national resilience efforts. The stakeholder analysis method allows for a structured assessment of the interests, influence, and coordination among governmental institutions, military entities, private sector actors, and international partners. This research demonstrates that integrating strategic intelligence with international cooperation is crucial for strengthening Indonesia's maritime security. It highlights the importance of intergovernmental agreements in addressing global challenges such as transnational crime in Southeast Asia. The study concludes that developing a strategic intelligence system is vital for realizing the vision of the Global Maritime Axis, emphasizing the need for coordinated efforts among government institutions and international cooperation to improve operational effectiveness in maintaining stability across Indonesia's maritime territories.